A Case of Anti-SAE1 Dermatomyositis - Max de Vries; Marco W. J. Schreurs; Els J. M. Ahsmann; Marcela Spee-Dropkova; Faiz Karim (Case Reports in Immunology)
Introduction. Anti-SAE1 antibodies have a low prevalence in dermatomyositis patients. Case Description. A 61-year-old woman presented with progressive shortness of breath, arthralgia, heliotrope rash, Gottron’s papules, and erythematous rash. She had an interstitial lung disease (ILD) with a significant decrease in lung function. There was no muscle involvement. Immunological laboratory test results showed strongly positive anti-SAE1 antibodies. Glucocorticoid treatment resulted in remission of dermatomyositis. Conclusion. Anti-SAE antibodies in dermatomyositis patients are closely linked to unique clinical features.